KEGIATAN LAPANGAN PROGRAM “Creative Action Camp: Pengembangan Karakter Inovatif melalui Experiential Learning” - Anggita Maharani; Nailah Amalia Fatihah; Izza Yulfana Khidismiya; Seftia Amanda Yustika (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This field activity aims to develop innovative character among rural youth through an experiential learning approach in the program